2022
DOI: 10.31223/x5sp6q
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The stabilizing effect of high pore-fluid pressure along subduction megathrust faults: Evidence from friction experiments on accretionary sediments from the Nankai Trough

Abstract: Highlights• Nankai accretionary sediments exhibit strong rate-strengthening friction behaviour• Frictional stability increases at high pore-fluid pressure: more rate-strengthening • Effective normal stress at constant pore pressure has minimal effect on stability • Elevated pore-fluid pressure may promote slow-or aseismic slip in subduction zones

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…Higher temperatures at deeper depths may lower the a‐b value for illite‐rich gouges (den Hartog & Spiers, 2013), meaning that the L c value for the inner prism might also be lower. The a‐b and d c values for the sediments in the Nankai Trough may depend on the effective normal stress and pore fluid pressure (Bedford et al., 2021); therefore, the estimated L c value may include some uncertainty because our experiments were conducted under hydrostatic conditions. Because our findings of a trench‐perpendicular pattern in velocity dependence and strength of the décollement match the spatial distribution of SSE occurrence and VLFE locations, the spatial variations in frictional properties of the sediment as well as pore pressure state may be responsible for the slip behavior at the shallow Nankai Trough subduction zone.…”
Section: Discussionmentioning
confidence: 99%
“…Higher temperatures at deeper depths may lower the a‐b value for illite‐rich gouges (den Hartog & Spiers, 2013), meaning that the L c value for the inner prism might also be lower. The a‐b and d c values for the sediments in the Nankai Trough may depend on the effective normal stress and pore fluid pressure (Bedford et al., 2021); therefore, the estimated L c value may include some uncertainty because our experiments were conducted under hydrostatic conditions. Because our findings of a trench‐perpendicular pattern in velocity dependence and strength of the décollement match the spatial distribution of SSE occurrence and VLFE locations, the spatial variations in frictional properties of the sediment as well as pore pressure state may be responsible for the slip behavior at the shallow Nankai Trough subduction zone.…”
Section: Discussionmentioning
confidence: 99%
“…Friction is a thermally activated process involving multiple micro‐physical mechanisms of deformation that control the frictional resistance in specific hydrothermal conditions (e.g., Bedford et al., 2021; Blanpied et al., 1995; Chester, 1994; Chester & Higgs, 1992; French et al., 2015; Niemeijer & Collettini, 2014; Xing et al., 2019, and references therein). Because of the extreme localization and grain comminution within fault zones, low‐temperature plasticity is the rate‐limiting process at the micro‐scale.…”
Section: Introductionmentioning
confidence: 99%
“…We have assumed an infinite gauge layer and observed that materials that are rate‐strengthening at steady state ( a > b ) can only feature delocalization of strain. This appears inconsistent with the widespread observation of faults and fault gauges that are more or less stable (e.g., Bedford et al., 2021; Carpenter et al., 2012; Coble et al., 2014; Ikari et al., 2011). A possible explanation is that a gauge layer is initially formed by a set of strain‐softening processes, subsequently chemically, petrologically, texturally or geometrically matured over time to become rate‐strengthening, but generally weaker than host rock.…”
Section: Discussionmentioning
confidence: 71%